Characterization of Respiratory Conditions Using Labview and Digital Spirometer - S. Noorjannah Ibrahim; A. Z. Jusoh; N. Abdul Malik; A. L. Asnawi; S. Mazalan (Institute of Advanced Engineering and Science, 2018)
One of the effective ways to diagnose various respiratory diseases is using spirometry test. Good spirometer comes with excellent graphical user interface. Spirometer is used to measure lung parameters such as Forced Expiratory Volume in the first second and the sixth seconds (FEV1 and FEV6). This paper presents an algorithm with Graphical User Interface (GUI) for characterization of respiratory conditions using LabVIEW Software. The whole spirometry system consists of a breathing circuitry with pressure sensor and a data acquisition board (NI sbRIO FPGA board). Results obtained from three different volunteers with different health performances are also presented in this paper. The FEV1/FEV6 ratio of a healthy volunteer is 81.1%, an asthma volunteer is 72.04%, and suspected bronchitis volunteer is 33.4%. Based on these results, the unhealthy volunteers tend to have smaller value of FEV1 with lower area under the curve when compared to healthy volunteer.